Party politics in Russia and Ukraine : electoral system change in diverging regimes - Moraski, Bryon (New York University Press, 2022)
Examines how political parties navigate major election reforms by comparing electoral system changes in Russia and Ukraine at the same time, under different regimes In Party Politics in Russia and Ukraine, Bryon Moraski provides a window into the political landscapes of Russia and Ukraine, two countries that have clashed with each other--and struggled with their own popular revolts--in recent years. Drawing on election outcomes, party nominations, parliamentary voting, and other data, Moraski highlights how ruling parties, incumbent legislators, and others have adapted to major electoral system changes in both countries.Moraski sheds light on how authoritarian regimes--and the ruling parties that support them--have used changing conditions in their countries to consolidate their power, with varying success. Exploring the swiftly changing political arena of Eastern Europe, Party Politics in Russia and Ukraine offers timely insight into the impact of elections in the twenty-first century.